Volatiles from male honeydew excretions attract conspecific male spotted lanternflies, Lycorma delicatula (Hemiptera: Fulgoridae) - Faal, Hajar; Meier, Linnea R.; Canlas, Isaiah J.; Murman, Kelly; Wallace, Matthew; Carrillo, Daniel; Cooperband, Miriam F. (Frontiers in Insect Science, 2022)
The spotted lanternfly (SLF), Lycorma delicatula (Hemiptera: Fulgoridae), is a generalist phloem feeder that produces copious amounts of honeydew, which in turn coats the understory. These insects form large aggregations covering the trunks of some trees, while similar trees nearby mysteriously seem unattractive. We investigated whether volatiles from SLF honeydew are attractive to conspecifics by collecting honeydew from the field and testing it for SLF attraction in a two-choice olfactometer. We found that honeydew excreted by adult male SLF was significantly attractive to male SLF, but not female SLF. Although the honeydew excreted by adult female SLF did not significantly attract male or female SLF, both sexes showed a positive trend towards attraction in response to female honeydew in the olfactometer. Analysis of the headspace volatiles of honeydew was conducted, and numerous semiochemicals were identified. Five of which, 2-heptanone, 2-octanone, 2-nonanone, benzyl acetate, and 1-nonanol, were tested in two-choice behavioral assays against a blank control. Benzyl acetate and 2-octanone were attractive to both sexes, whereas 2-heptanone was only attractive to males, and 2-nonanone only to females. The remaining compound, 1-nonanol, repelled females, but not males. Although honeydew has been reported as a source of kairomones for some natural enemies, this may be the first report of sex-specific attractants for conspecific insects found in the honeydew volatiles of a planthopper.